Several documents on German and Georgian cooperation during the interwar period and World War II are kept in the Polish archives in London – Part II - Adamczewski, Przemysław (Sensus Historiae, 2019)
The paper presents documents on the German and Georgian cooperation during the interwar period and World War II kept in the Polish archives in London. One of the documents, written by Edmund Charaszkiewicz, can be treated as a potential clue in the thesis that individual Georgian military men might have been agents of the German intelligence service, which also used Georgian emigrants with right- wing views who lived in Poland for its purposes. Another document, written by Simon Kobiaszwili, is dedicated to the explanation of what caused that some of the Georgian emigrants who stayed in Europe developed collaboration with the Germans during World War II. To a great extent, the paper also discusses the conflict in the community of Georgian emigrants in the interwar period and the policy of the Polish authorities toward the Georgian government in exile established by socialists.